“Tú me quieres blanca”. El mito de la pureza lingüística en la escuela argentina - López García, María (Enunciación, 2021)
Among the linguistic myths of the Spanish language, purity seems to be the most prevalent among Argentine speakers, as well as the most productive metaphor to generate representations about the possible existence of a common language. This article reviews some topics related to the myth of linguistic purity in Argentine schooling since the enactment of the first education law in 1884.